Purchasing Power Parity in the Case of Romania; Evidence from Structural Breaks - Ocal, Oguz (International Journal of Economics and Financial Issues, 2013)
Purchasing Power Parity has most likely been one of the most investigated issues of the last decades within economic literature. The results from such studies are not consistent and not only important for policy makers and economists but also extremely important for policy implications in international finance. Purchasing Power Parity states the exchange rate between two countries should reflect the relative purchasing power of these two countries. This study tests the validity of the purchasing power parity hypothesis in Romania with employing Zivot–Andrews unit root test by taking structural break into account. We use annual data from 1991 to 2012 and the results show that purchasing power parity does not hold in Romania. Keywords: Purchasing power parity; real exchange rates; structural breaks JEL Classifications: F30; F31